2008
DOI: 10.1128/mcb.00306-08
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Identification of MAZ as a Transcriptional Regulator of Muscle-Specific Genes in Skeletal and Cardiac Myocytes

Abstract: We identified a conserved sequence within the Muscle creatine kinase (MCK) promoter that is critical for high-level activity in skeletal and cardiac myocytes (MCK Promoter Element X [MPEX]). After selectively enriching for MPEX-binding factor(s) (MPEX-BFs), ICAT-based quantitative proteomics was used to identify MPEX-BF candidates, one of which was MAZ (Myc-associated zinc finger protein). MAZ transactivates the MCK promoter and binds the MPEX site in vitro, and chromatin immunoprecipitation analysis demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 82 publications
1
62
0
Order By: Relevance
“…MAZ (mycassociated zinc-finger protein) has been shown to regulate musclespecific gene expression. 30 RP58 has an essential role in skeletal myogenesis, 31 and BLIMP1 is involved in myocyte differentiation. 32 CIZ is implicated in regulation of bone mass biology.…”
Section: Discussionmentioning
confidence: 99%
“…MAZ (mycassociated zinc-finger protein) has been shown to regulate musclespecific gene expression. 30 RP58 has an essential role in skeletal myogenesis, 31 and BLIMP1 is involved in myocyte differentiation. 32 CIZ is implicated in regulation of bone mass biology.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach for studying TF-TRE interactions that does not require genetic engineering or protein detection reagents, and can readily provide information about the ensemble of TFs associated with a TRE, is DNA affinity purification followed by "shotgun" mass spectrometry (MS) analysis (8)(9)(10). This approach takes advantage of the ability of MS to identify large numbers of proteins in complex mixtures, and, when performed in a quantitative manner, can identify specific TF-DNA binding events even in the presence of a high background of nonspecifically copurifying proteins.…”
mentioning
confidence: 99%
“…The reporter plasmids Ϫ80MCKCAT, eϪ80MCKCAT, Ϫ358MCKCAT, eϪ358MCKCAT, (MPEX-mt)Ϫ80MCKCAT, and pUCSV2PAP have been described previously (1,25,54), as have constructs containing full-length mouse KLF3 cDNA in pMT2 (12), full-length and all truncated mouse KLF3 cDNAs in pMT3 (46), FLAG-tagged mouse KLF3 cDNA in pMT3 (46), and full-length KLF4 cDNA in pcDNA3 (a generous gift of Gary Owens [35]). Full-length human SRF cDNA in pCGN (11) was a generous gift of Robert Schwartz.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we used quantitative proteomics to identify factors binding the MCK promoter MPEX site and demonstrated that one of these candidates, MAZ, regulates muscle-specific genes through both established and divergent binding motifs (25). Here, we investigate the role of Kruppellike factor 3 (KLF3), which was also identified as a candidate MPEX-binding factor (MPEX-BF) by proteomic analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation